2010
DOI: 10.2118/129329-jpt
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Wormholes in Carbonates: Unprecedented Experimental Scale and 3D Visualization

Abstract: Technology Today Series articles are general, descriptive representations that summarize the state of the art in an area of technology by describing recent developments for readers who are not specialists in the topics discussed. Written by individuals recognized as experts in the area, these articles provide key references to more definitive work and present specific details only to illustrate the technology. Purpose: to inform the general readership of recent advances in various areas of petroleum engineerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Matrix acidizing (with acid concentration of up to 15%) commonly enhances production by increasing the effective wellbore radius and causing stimulation as seen in earlier large scale studies [7]. Matrix acidizing experiments combined with visualization techniques are commonly used to study the details of wormhole networks formed during matrix acidizing of carbonates [8]. Several treatment parameters such as acid injection rate, acid concentration, and variation of rock permeability, reservoir temperature and acid volume injected are optimized to execute an efficient acidizing job in carbonate reservoirs [9][10].…”
Section: Conventional Low-concentration Acidizingmentioning
confidence: 99%
“…Matrix acidizing (with acid concentration of up to 15%) commonly enhances production by increasing the effective wellbore radius and causing stimulation as seen in earlier large scale studies [7]. Matrix acidizing experiments combined with visualization techniques are commonly used to study the details of wormhole networks formed during matrix acidizing of carbonates [8]. Several treatment parameters such as acid injection rate, acid concentration, and variation of rock permeability, reservoir temperature and acid volume injected are optimized to execute an efficient acidizing job in carbonate reservoirs [9][10].…”
Section: Conventional Low-concentration Acidizingmentioning
confidence: 99%
“…At the opposite end of the spectrum, we perceive further opportunities to design experiments in the subsurface or in large laboratory facilities to learn more about deformation and fluid-rock interaction behaviours over larger volumes. For example, McDuff et al (2010) demonstrated the benefits from experiments on wormhole formation via the non-destructive imaging of large (c. 0.5 m 3 ) blocks of carbonate rock.…”
Section: Selected Advancesmentioning
confidence: 99%
“…The acid type affects the structure of wormholes generated during carbonate acidizing [7,12]. Slow reacting acids, such as chelating agents and other organic acids form wider, less branched wormholes, while highly reactive acids, such as HCl, form highly branched wormholes [13]. The relative magnitudes of acid transport and reaction rates define the controlling step of the dissolution reaction whether kinetically controlled or mass-transfer controlled [14].…”
Section: Introductionmentioning
confidence: 99%